2004
DOI: 10.1007/s00464-003-9230-6
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed laparoscopic cholecystectomy for acute cholecystitis: a prospective randomized trial

Abstract: Early laparoscopic cholecystectomy for acute cholecystitis is safe and feasible, offering the additional benefit of a shorter hospital stay. It should be offered to patients with acute cholecystitis, provided the surgery is performed within 72 to 96 h of the onset of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
238
3
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(277 citation statements)
references
References 14 publications
25
238
3
11
Order By: Relevance
“…6 Timing of LC for AC has been controversially discussed. [22][23] In the past, many authors argued that early LC for AC is associated with a high risk of complications. In 1992, Frazee et al 17 declared AC as a contraindication for LC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Timing of LC for AC has been controversially discussed. [22][23] In the past, many authors argued that early LC for AC is associated with a high risk of complications. In 1992, Frazee et al 17 declared AC as a contraindication for LC.…”
Section: Discussionmentioning
confidence: 99%
“…The median duration of surgery for this study was 37 minutes (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) minutes. The corresponding values were 36 minutes (11-221) minutes and 39 minutes (12-159) minutes for the female and male group, respectively.…”
Section: Duration Of Surgerymentioning
confidence: 99%
“…1 However, in the early days, acute cholecystitis was a contraindication of laparoscopic cholecystectomy, and patients with acute cholecystitis were managed conservatively and discharged for re-admission in order to have elective surgery performed for the definitive treatment. 2,3 Then, randomized controlled trials and meta-analyses had shown the benefits of early surgery (within the acute admission period, which is 24 to 72 hours) compared with delayed cholecystectomy with respect to hospital stay and costs, with no significant difference in morbidity and mortality.…”
mentioning
confidence: 99%
“…Although an open approach remains a valid option in complicated cases (e.g., gangrenous cholecystitis, etc. ), LC is reportedly safe and beneficial according to most series [4][5][6][7][8]. As the latter are issued from experts, they may not reflect general surgical practice, in particular regarding overall mortality and biliary complication rate.…”
mentioning
confidence: 99%